The Application of Dual‐Layer, Mussel‐Inspired, Antifouling Polyglycerol‐Based Coatings in Ventricular Assist Devices. Issue 21 (6th September 2020) - Kulka, Michaël W.; Smatty, Sarah; Hehnen, Felix; Bierewirtz, Tim; Silberreis, Kim; Nie, Chuanxiong; Kerkhoff, Yannic; Grötzinger, Carsten; Friedrich, Sebastian; Dahms, Lars Ingemar; Dernedde, Jens; Grunwald, Ingo; et al.
Abstract: Continuous‐flow ventricular assist devices (VADs) have established themselves as a lifesaving therapy option in patients with severe cardiovascular disease. Unfortunately, complications with VADs resulting from the shear‐induced formation of surface blood clots are common. In the current work, an antifouling coating based on the combination of mussel‐inspired dendritic polyglycerol (MI‐dPG) and linear polyglycerol (lPG) is tested for its cell‐repelling properties, biocompatibility, and complement activating properties. Furthermore, the adhesion and activation of blood platelets are tested under static and flow conditions. The adhesion and proliferation of two cell types are studied by means of LIVE/DEAD cell staining, and it is clearly observed that the lPG‐functionalized MI‐dPG coating prevents cell adhesion. Additionally, no cell mortality is observed on all substrates, indicating the biocompatibility of the tested coatings. All coatings show lower (or equal) complement‐activating properties than bare titanium, which is considered a highly biocompatible material. Most importantly, the lPG‐functionalized system prevents the adhesion and activation of blood platelets under static and flow conditions. Finally, a prototype VAD is successfully coated with MI‐dPG under flow conditions. In the current study, the efficient lPG‐functionalization of the MI‐dPG coating is proved to obtain cell‐ and platelet‐repelling surfaces. Abstract : The current work investigates the biocompatibility and the cell‐ and platelet‐repelling properties of an antifouling coating based on the combination of mussel‐inspired dendritic polyglycerol and linear polyglycerol. The results are compared to a similar mussel‐inspired poly(ethylene glycol)‐functionalized coating. The platelet repelling properties of the coatings are shown under static and medically relevant flow conditions.